2012
DOI: 10.1093/geronb/gbr153
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age Stereotypes on Self-perceptions of Aging Across the Adult Lifespan

Abstract: Taken together, although we find some support for contrast effects, most of our results can be interpreted in terms of assimilation effects, suggesting that individuals integrate stereotypical information into their self-evaluations of age(ing) when confronted with stereotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(133 citation statements)
references
References 41 publications
8
116
2
7
Order By: Relevance
“…In summary, stereotypes of aging are pervasive in our culture and they have been found to influence how older adults see themselves [22,[74][75][76]; how older adults view other older adults (social comparison and beliefs about old age) [8,15,22]; older adults' cognitive and physical performances [16,25,26,28,29,37,55,77]; the ability of older adults to recover from disease [78]; older adults' health behaviors, including their decisions to engage in cognitive, social, and physical activity [1,4,21,65,79] and/or seek medical assistance [33,35,53,80]; as well as how older adults are treated by others and society as a whole [1,3,4,7,[81][82][83].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, stereotypes of aging are pervasive in our culture and they have been found to influence how older adults see themselves [22,[74][75][76]; how older adults view other older adults (social comparison and beliefs about old age) [8,15,22]; older adults' cognitive and physical performances [16,25,26,28,29,37,55,77]; the ability of older adults to recover from disease [78]; older adults' health behaviors, including their decisions to engage in cognitive, social, and physical activity [1,4,21,65,79] and/or seek medical assistance [33,35,53,80]; as well as how older adults are treated by others and society as a whole [1,3,4,7,[81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…To complicate and extend these findings, however, other studies have shown that explicit positive aging stereotypes can have constraining effects on older people's attitudes and health behavior and that negative aging stereotypes can be resisted by older adults resulting in enabling effects such as feelings of personal empowerment and associated health benefits [8,15,22,23].…”
Section: How Stereotypes Work To Affect Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Often there is a discrepancy between how old a person feels and his/her actual age; the age people perceive themselves to be is referred to as a subjective age (Kotter-Gruhn and Hess, 2012). There has been much written about the stigma associated with aging in today's youth-driven society (Schoemann and Branscombe, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Otros autores defienden el uso de los medios de comunicación en las estrategias que aboguen por los derechos humanos económicos, sociales, culturales y de participación de los adultos mayores, en particular en lo relativo a contrarrestar la imagen cultural estereotipada negativa que predomina de ellos (Casapié, Balbontín, Porras & Mateo, 2011;CNTV, 2005CNTV, , 2010Medina & Zorrilla, 2011;Kotter-Gruhn & Hess, 2012;De Andrés & Maestro, 2013). La estimulación mediante la comunicación de procesos y funciones cognitivas se considera un aspecto relevante de la salud y la calidad de vida del adulto mayor (Martín, Aguado, Díaz & Lorience, 2000;González, García & Mata, 2012), así como la promoción del contacto a través del uso de computadores (Dickinson & Hill, 2007).…”
Section: Comunicación Y Salud Para Los Adultos Mayores: De La Mano Counclassified